Effectiveness of teleworking using internet facilities (E-Teleworking) - Awang, M Khalid; Hassan, Hasni; Mat Amin, Maizan; W A Halim, W Faranaquiah (2005)
Teleworking offers alternatives for people to work without concerning their geographical boundary or time zone. Work can be performed anywhere and anytime without restriction.Teleworking tends to be the trend in the world of business.However, in spite of its popularity, Malaysia is still lagging behind in its implementation.Telecommunication technology is the key factor in contributing to the successful implementation of teleworking.In order to carry out the task of teleworking,a variety of telecommunication facilities are available.However, nowadays, only one approach is considered effective that is using the Internet facilities (e-teleworking).The main objective of the research is to evaluate the effectiveness of e-teleworking. In depth literature review had been done in recognizing the traits of teleworking that can be implemented using Internet facilities.A prototype of e-teleworking had been developed as a tool in the evaluation phase. The findings had proven that Internet facilities are indeed one of the most effective alternatives in performing teleworking.